Levels of carnitine and acylcarnitines in reconstituted red blood cell samples washed with different concentrations of saline solutions - JOSÉ HENRY OSORIO (Colombia Médica, 2010)
Objective: To evaluate the percentage of carnitine and acylcarnitines remaining in red blood cells after washing them with different concentrations of saline solution. Materials and methods: Human blood samples were centrifuged and the blood cells were washed with different saline solutions. The final pellet was resuspended in PBS for card preparation and tandem mass spectrometry analysis. Results: It was found that carnitine, as well as short-chain, medium-chain, and long-chain acylcarnitines remain in red blood cells at average percentages of 19.3; 34; 34; and 32%, respectively. Significant differences were found for carnitine and acylcarnitine levels in blood washed with an isotonic solution compared to their levels using several hypotonic solutions (p<0.05). Conclusion: Because carnitine and acylcarnitines remained associated with the blood cells, we recommend using whole blood to measure these metabolites.